Feet back on the ground - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Thomas Tchibinda of Cotonou, Benin, is worried about Spore's euphoria' about Southern farmers wanting to get a place in the new planetary village that the world is turning into, thanks to ICTs and the World Trade Organisation. He urges us to...